Merancang Media Sosial sebagai Sarana Promosi Perpustakaan SMAN 13 Bandung - Lulu Mutiara; Ninis Agustini Damayanti; Samson CMS (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
Introduction. SMAN 13 Bandung Library does not yet have digital media as a means of disseminating information and promoting services, so information is only delivered through printed media such as bulletin boards. This study aims to design an Instagram social media account as a medium for information and promotion of library services to reach more students.. Data Collection Methods. The method used is action research with the Kurt Lewin model which consists of the planning, action, observation and reflection stages. Data Analysis. Data were obtained through observation, interviews, documentation, and questionnaires. The results of the study indicate that the Instagram account @perpustakaan.sman13bdg has succeeded in providing library service information in an interesting, informative, and easy-to-understand manner. Results and Discussion. Based on the questionnaire distributed to 107 students, all success indicators showed a satisfaction percentage above 89%, indicating that social media is effective as a means of library promotion. The librarian's response also supports that the designed account has met user needs. Conclusion. Instagram accounts can be an effective and relevant information media in bringing library services closer to students and increasing the appeal of school libraries. The suggestions in this study are (1) continuous content development (2) periodic evaluation (3) student involvement in content creation (4) Social Media Management Training for Librarians.